Personal culture dan integritas, mana yang lebih penting untuk mengurangi kecurangan akuntansi? - Adhivinna, Vidya Vitta; Aprilia, Irma (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2021)
ABSTRACT: The research aimed to get empirical evidence the influence of internal control, individual morality, personal culture and integrity on accounting fraud at the OPD of Kulon Progo Regency. The sample used was 69 respondent with puropsive sampling method. The data were analized with multiple linear regression. The results of this reserch show that the personal culture has a positive effect on the accounting fraud and integrity has a negative effect on the accounting fraud, while internal control and has no effect on the accounting fraud.